Self-Concept, Gender Equality, and Discrimination in Physical Education: Analysis by Sex in Secondary Education; Autoconcepto, Igualdad de Género y Discriminación en Educación Física: Análisis por Sexo en Educación Secundaria - Farias-Valenzuela, C (Universidad Autonoma de Chile, 2025)
Gender equality remains a critical focus in educational discourse. This study investigates sex-based differences and the interrelations among self-concept, perceived gender equality, and discrimination in physical education among secondary school students. A sample of 418 students was assessed using the Perception of Equality and Discrimination in Physical Education Questionnaire and the AF5 Self-Concept Scale. The analysis employed Mann–Whitney U tests, Spearman’s correlations, and regression modeling. Findings show that male students report higher physical, social, and family self-concept, while female students show greater emotional self-concept. Age correlates with increased discrimination and reduced academic and emotional self-concept in males, whereas in females, it associates with higher perceived equality and lower social self-concept. Perceived equality inversely correlates with discrimination and positively with academic self-concept across both sexes. Regression results indicate that discrimination, along with academic, social, and family self-concept, positively predicts physical self-concept, whereas emotional self-concept and sex have negative predictive effects. These insights inform educational interventions and teacher training programs to foster gender equity and self-concept development in school settings. © 2025 Universidad Autonoma de Chile. All rights reserved.
Keywords: gender equality; discrimination; self-concept; physical education; secondary education